IMPLEMENTASI E-COMMERCE PADA TOKO SEPEDA CENTIMETER MENGGUNAKAN FRAMEWORK LARAVEL DENGAN MODEL WATERFALL BERBASIS WEBSITE - Iwank Ravi Eka Sakristi; Niki Ratama (Journal of Research and Publication Innovation, 2023)
The development of the world of technology and information is getting faster day by day. These developments clearly affect the speed and accuracy of information delivery. Unfortunately, there are still many business activities, especially the buying and selling process, which are not in line with current technological advances. On that basis, the author tries to make a final project regarding the implementation of e-commerce in a bicycle shop, which currently sells manually and traditionally. Most sales systems that run at bicycle shops are done manually, starting from product offerings, sales of goods, and recording transaction history, so that during the process there is an error in recording. The implementation of this e-commerce sales system is the best solution to overcome the problems that occur in bicycle shops. For the software development method, the author uses the waterfall model. In making this sales application using a programming language using PHP, Laravel framework and using a MySQL database. The expected results from the creation and implementation of this sales application are able to provide information quickly and precisely. It is hoped that with this application, users can increase profits in their business.